Improving vocabulary performance of high school deaf/hard-of-hearing students using preteaching strategy - Mondejar, Magdalena C. (College of Education, University of the Philippines Diliman, 2019)
Deaf/Hard-of-Hearing students' struggle with reading comprehension is closely linked with vocabulary knowledge. Researches revealed that lack of vocabulary knowledge and grammar of the spoken language are primarily the cause of reading problems among deaf individuals (Apel, & Masterson, 2015; Kyle & Harris, 2006; Lonigan, 2015; Marschark, & Spencer, 2010). In response to this need, a number of researches specifically techniques and strategies to teach vocabulary were investigated. However, despite efforts on discovering effective strategies, researches remain to be limited (Marschark, & Spencer, 2010). This study intended to contribute to the body of research on finding effective teaching strategy to improve vocabulary of D/HH students. Specifically, this study explored the use of preteaching teaching strategy in improving the vocabulary performance among D/HH students. This study investigated if there was a functional relation on the participants' signing, matching, and fingerspelling performances after undertaking eight weeks of intervention sessions. The independent variable was preteaching, while the dependent variables were the number of vocabulary words signed, matched, and fingerspelled correctly during posttests. A total of 10 Grade 7 D/HH students ages 12 to 27 participated in the study, via convenience sampling. Multiple-baseline design (ABC) across three sets of five vocabulary words was used in this study. Findings were interpreted using visual analysis and Wilcoxon Signed Rank Test. Participants' perception regarding the program were also gathered through focus group discussion. After the intervention sessions, results indicated that eight out of 10 participants signed, matched, and fingerspelled 80% to 100% of the targeted vocabulary words. Recommendations for teachers, parents, school administrators, and future researchers are discussed.